The study of the Tualang honey viscosity - Abd. Rahim, Nour El Huda; Zulkifly, Ahmad Hafiz; Mohamed, Farahidah; Ku Zaifah, Norsidah (2012)
Honey had been mentioned in the Holy Quran as a healing for men in Surah An Nahl, 16:68-69. Almost 50 hadiths showed its health significance. The objective of this study was to explore the viscosity of Tualang honey, an important characteristic for development of a pharmaceutical product. Tualang honey was investigated for its viscosity at different temperatures (25, 37 and 40°C). The effect of temperatures on viscosity needs to be evaluated due to a wide range of temperatures encountered during processing and storage of pharmaceutical products. In a plot of shear rate against shear stress, Tualang honey produced linearity with straight line going through zero in all temperatures. The viscosity remained constant by increasing shear rate. This profile was consistent with the behaviour of a simple fluid which is Newtonian fluid. For the apparent viscosity of the Tualang honey, there was no significant difference (p>0.05) in all temperatures (25°C=1.21±0.67 Pas, 37°C=1.22±0.53 Pas and 40°C=1.02±0.56 Pas). These results suggested that Tualang honey had a Newtonian fluid characteristic. It also did not show any significant difference in the viscosity when increasing the temperature implying that the loss of water content was not significant and the protein did not denature. In conclusion, the Newtonian behavior of Tualang honey and its effect on the temperatures are expected to facilitate the process of Tualang honey into pharmaceutical products in the future.